Postnatal Management in Congenital Lower Urinary Tract Obstruction With and Without Prenatal Vesicoamniotic Shunt - Jank, Marietta; Stein, Raimund; Younsi, Nina (Frontiers in Pediatrics, 2021)
Abstract Purpose Congenital lower urinary tract obstruction (cLUTO) includes a heterogeneous group of conditions caused by a functional or mechanical outlet obstruction. Early vesicoamniotic shunting (VAS) possibly reduces the burden of renal impairment. Postpartum, pediatric urologists are confronted with neonates who have a shunt in place and a potentially impassable urethra with a narrow caliber. Early management of these patients can be challenging. Here, we would like to share the approach we have developed over time. Materials and Methods We conducted a single-center retrospective analysis from 2016 to 2020 and included all patients diagnosed with cLUTO. Data focusing on time point and type of intervention was collected. Furthermore, patients with temporary diversion via a percutaneous VAS were selected for a more detailed review. Results In total, 71 cases of cLUTO were identified during the study period. Within this group, 31 neonates received postnatal management and surgical intervention in our center. VAS was performed in 55% of these cases (N=17). The postnatal treatment varied between transurethral or suprapubic catheterization and early Blocksom vesicostomy. In 5 infants with a VAS, the urinary drainage was secured through the existing VAS by inserting a gastric tube (N=1) or a 4.8 Ch. JJ-stent (N=4). To our knowledge, this is the first report of a stent-in-stent scheme, which can remain indwelling until the definite treatment. Conclusion Having a secure urine drainage through a VAS allows the often premature infant to grow until definite surgery can be performed. This avoids placing a vesicostomy, which requires anesthesia.